The dynamics of public spending - Thomas R. Cusack (Wissenschaftszentrum Berlin für Sozialforschung (WZB); Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1992)
This paper provides a model-based account of the forces shaping the dynamics of government spending in the industrialized democracies over the past few decades. The principle argument is that both short-term and long-term forces have been at work in the evolution of government spending in these countries. Emphasized here is the important role that the prevailing center of political gravity within the polity as well as the constraints that recent movements toward the integration of national capital markets into the international economic system have played in bringing about changes in government spending levels. Incorporated in the model are the hypothesized effects, in both the short and long run, of a set of cointegrated independent variables, as well as a set of other terms with impacts that are likely to be short run. The hypotheses surrounding this formulation are systematically tested and then a more encompassing model that includes the effects of domestic politics and international economic conditions is then presented and evaluated. – – Dieser Beitrag bietet anhand von Modellen einen Uberblick iiber die Krafte, die der Dynamik der offentlichen Ausgaben in den industrialisierten Demokratien in den vergangenen Jahrzehnten zugrundelagen. Die Hauptthese ist, daB sowohl langfristige wie auch kurzfristige EinfluBe die Entwicklung der Regierungsausgaben in diesen Landern bestimmt haben. Zwei Einfliisse haben cine besondcre Rollc bei der Veranderung der Struktur der offentlichen Ausgaben gespielt: die in den politischen Gemeinschaften jeweils dominierende Mitte und in jiingster Zeit der eingeschrankte Spielraum auf Grund der zunehmenden Integration der nationalen Kapitalmarkte in das international okonomische System. Das Modell umfaBt angenommene kurz- und langfristige Auswirkungen in Form eines Satzes kointegrierter unabhangiger Variablen sowie einen Satz anderer Variablen mit angenommenen kurzfristigen Auswirkungen. Die zugrundcliegenden Hypothesen werden systematisch getestet; dann wird ein umfangreicheres Modell, das die Auswirkungen von Innenpolitik und international Wirtschaflsbedingungen einbezieht, vorgestellt und ausgewertet.
Keywords: 320